Relationship between diarrhea history, exclusive breastfeeding, and feeding patterns with stunting incidence in toddlers aged 24-59 months - Jamilatul Wahida; Candra Bumi; Citra Anggun Kinanthi (Universitas Udayana, 2025)
Background and purpose: Stunting remains a major public health issue globally, including in Jember District. Despite the significant stunting reduction in the region—from 21.4% in 2020 to 6.6% in 2024—Rambipuji Public Health Center (PHC) reports a comparatively high prevalence of 19.94%, indicating a persistent public health concern. This study aimed to analyze the association between diarrheal history, exclusive breastfeeding, and feeding patterns with the incidence of stunting among children aged 24–59 months. Methods: An analytical observational study with a case–control design was conducted among 114 children aged 24–59 months (57 cases and 57 controls) selected by simple random sampling in the Rambipuji PHC area based on growth monitoring data from May 2025. Data which include stunting status, children characteristics and maternal characteristics were collected through structured interviews and observations, and analyzed using chi-square tests (α=0.05) with SPSS. Results: The results indicated significant associations between maternal education (OR=11.25; 95%CI: 1.354-93.504; p=0.026), exclusive breastfeeding (OR=3.352; 95%CI: 1.377-8.159; p=0.006), and feeding patterns (OR=10.5; 95%CI: 2.336-47.201; p=0.005) with stunting incidence. However, a history of diarrhea was not significantly associated with stunting. Conclusion: Maternal education, exclusive breastfeeding, and feeding patterns are associated with stunting among children. Strengthening maternal nutrition and feeding education, as well as optimizing services at integrated health posts (Posyandu) and public health centers (Puskesmas), are essential to reduce stunting prevalence.